Survey of high school librarians' salary in Quezon City - Esteban, Amelia H. (1993)
This research study aims to investigate the salary ranges of private and public high school librarians in Quezon City. Problems in salary condition, school's policy on librarian's salary and position of the library in the organizational structure of the school are included in the objectives as well.